Science in the ancient world : from antiquity through the middle ages - Lawson, Russell M., 1957- (Santa Barbara, California : ABC-CLIO, 2021)
"Explores the history of science in the ancient world from prehistory through roughly 1300 CE, looking not just at Greece and Rome but at developments in Africa, Asia, and the Americas as well"--
Part 1. The beginnings of science. The scientific mentality before the onset of civilization (prehistory - 4000 BCE) -- Civilization and science in ancient Mesopotamia (4000 - 300 BCE) -- Civilization and science in the Nile River Valley (3100 - 300 BCE) -- Part 2. Magic, religion, and science. Magic, superstition, and science in the ancient world (4000 BCE - 500 CE) -- Ancient religion and science (4000 BCE - 500 CE) -- Part 3. Science in ancient central, southern, and eastern Asia. Science in ancient central and southern Asia (3000 BCE - 500 CE) -- Science in ancient eastern Asia (2100 BCE - 400 CE) -- Part 4. The ancient Greeks. Ionian Greek science (750 - 300 BCE) -- Science in Magna Graecia (750 - 300 BCE) -- Classical Greek science (500 - 300 BCE) -- Athenian science (500 - 300 BCE) -- Part 5. Geographical and astronomical knowledge. Exploration and geographical knowledge in the ancient world (4000 BCE - 500 CE) -- Phoenician and Carthaginian science (1000 - 200 BCE) -- Astronomy in the ancient and medieval worlds (4000 BCE - 1500 CE) -- Part 6. The expansion of Greek science. Hellenistic Greece (331 - 30 BCE) -- Greek philosophy and the philosophy of science (750 - 100 BCE) -- Greek science in the Roman Empire (750 BCE - 500 CE) -- Part 7. Greco-Roman science. Medical science in ancient Greece (750 - 100 BCE) -- Medical science in the Roman Empire (300 BCE - 500 CE) -- Mathematical science in ancient Greece and Rome (750 BCE - 200 CE) -- Science during the Pax Romana (31 BCE - 180 CE) -- Part 8. Applied science in the ancient and medieval worlds. Engineering and technology in the ancient and medieval worlds (4000 BCE - 1500 CE) -- Social and behavioral sciences in the ancient and medieval worlds (500 BCE - 1500 CE) -- Part 9. Science in the later Roman and Byzantine empires. Late Roman science (180 - 500 CE) -- Byzantine science (300 -1450 CE) -- Part 10. The impact of ancient science upon medieval Asia, Africa, and Europe. Science in medieval Mesopotamia and the Levant (600 - 1500 CE) -- Science in Moorish Spain (700 -1450 CE) -- Science in medieval Africa (500 - 1500 CE) -- Science in medieval central and southern Asia (500 - 1500 CE) -- Science in medieval east and southeast Asia (400 - 1644 CE) -- Science and philosophy during the European middle ages (500 - 1300 CE) -- Part 11. Expansion of science into new worlds. Exploration and geographic knowledge in the medieval world (500 - 1500 CE) -- Science in the Americas (500 - 1500 CE) -- Part 12. The impact of ancient and medieval science upon modern science. Conclusion: The scientific revolution.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 19, 2021).
eBooks on EBSCOhost
Keywords: Science, Ancient -- Encyclopedias; Science, Medieval -- Encyclopedias; Sciences anciennes -- Encyclopédies.; Sciences médiévales -- Encyclopédies.; Science, Ancient; Science, Medieval; Encyclopedias